2018
DOI: 10.1016/j.jbusres.2018.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Applying positive psychology to selling behaviors: A moderated–mediation analysis integrating subjective well-being, coping and organizational identity

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 121 publications
2
19
0
1
Order By: Relevance
“…First, we demonstrate that adaptive selling behavior is driven by the salesperson's abilities to self-monitor and selflead himself/herself through a cognitive process that could Figure 2 Moderating effect of sensitivity to expressive behaviors of other and thought self-leadership strategies on adaptive selling behavior lead to higher levels of behavioral performance. Recently, several researchers have explored the role of positive psychology in enhancing the effectiveness of selling behaviors (Lyngdoh et al, 2018). Within this context of linking positive psychology to selling behaviors and outcomes, our study further strengthens its integration into a sales literature.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…First, we demonstrate that adaptive selling behavior is driven by the salesperson's abilities to self-monitor and selflead himself/herself through a cognitive process that could Figure 2 Moderating effect of sensitivity to expressive behaviors of other and thought self-leadership strategies on adaptive selling behavior lead to higher levels of behavioral performance. Recently, several researchers have explored the role of positive psychology in enhancing the effectiveness of selling behaviors (Lyngdoh et al, 2018). Within this context of linking positive psychology to selling behaviors and outcomes, our study further strengthens its integration into a sales literature.…”
Section: Discussionsupporting
confidence: 68%
“…Further, we provide additional explanation to strengthen the arguments linking positive psychology to adaptive selling behaviors. This vein of inquiry addresses calls for research to place a sharper focus on positive valance variables and their role in driving salesperson's behaviors (Panagopoulos and Ogilvie, 2015;Friend et al, 2016;Lyngdoh et al, 2018).…”
mentioning
confidence: 99%
“…Another category we added to Verbeke’s framework was “job-related psychosocial factors.” By psychosocial factors we refer to work conditions, work roles, job-related interpersonal relationships, etc., leading to stress and health disorders. Broadly, three sub-categories were identified in the paper – “psychological demands,” “job control” and “work-related social support.” There is clear evidence that the lack of these factors is forcing the salesforce to embrace spirituality and positivity (Chawla and Guda, 2010; Lyngdoh et al , 2018). Hence, we propose that there should be a stream of research scholars in the sales management domain exploring the facets of positive psychology, which deals with the study of positive emotions, positive character traits and enabling institutions (Seligman and Csikszentmihalyi, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Fredrickson (2013) identified improvements in individuals’ well-being brought about through positive interventions. Chawla and Guda (2013) and Lyngdoh et al (2018) found that spirituality and happiness help salespeople to improve their performance. They posited that positive emotions help build flexibility in thinking and help salespeople to be innovative, adaptive and customer-centric.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation